Internationalization and Diversification Strategies of Agricultural Cooperatives: a Quantitative Study of the Agricultural Cooperatives in the State of Parana - Claudia Monica Ritossa; Sergio Bulgacov (BAR: Brazilian Administration Review, 2009)
This study investigates the impact of internationalization on the results achieved by agricultural cooperatives in the State of Parana, at the same time examining strategies for diversification of markets as well as diversification of products aimed exclusively at international markets. Of the 28 cooperatives to be included in the study, 67.9% returned valid structured questionnaires. The collected data was submitted to non-parametric statistical analysis. Key findings suggest the following: external markets are served by indirect and direct exports; product diversification strategies are motivated by the creation of revenue alternatives to members and by the reduction of risks associated to agricultural business; diversification strategies are conceived to develop new business in accordance with market demand and to expand customized products from the existing portfolio; the formation of strategic alliances prioritizes access to distribution channels abroad; internationalization and diversification strategies produce positive results both from an economic and a social perspective.